Soil and Water Conservation Programme-Implementation through Minority and Regional Languages - Pandey, C.M. (Journal of Soil and Water Conservation, 2022)
Land Resources Survey of India reveals that total geographical area of the country is 329 m.ha. These land resources are thus limited, where as demands for different type of land uses, like net sown area, irrigated area, area underforest, pasture, urbanisation etc. are increasing day by day due to increased population of the country. The above increased demands are resulting, in availability of less land per capita. It has been estimated that the availability of total land per capita would decrease from 0.89 ha. (1980) to 0.33 ha. by 2000 A.D. Implementation of an action plan supported by a policy drawn at the highest level will need all act together. But in any catchment very large number of persons concerned may speak only minority language. Thus guidellines and other instructions should be transmitted through such languages. [Thus, land being limited, its optimum utilisation, become essential to meet the requirements of primary production system as well as social needs with the rising population and enlarging aspiration of communities. The soil and water conservation programmes are implemented through State Governments by involving the inhabitants of the areas, which can further ensure if instructions/guidelines are provided in minority or regional languages. This will provide psychological satisfication and also encourage in better catchment community participation in programme formulation, implementation and post programme care and would finally create a feeling amongst all in the catchment community that these are their own programme rather than a programme imposed by the Government.]